2020
DOI: 10.3390/microorganisms8071017
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviruses and T1D: Is It the Virus, the Genes or Both which Cause T1D

Abstract: Type 1 diabetes (T1D) is a chronic autoimmune disorder that results from the selective destruction of insulin-producing β-cells in the pancreas. Up to now, the mechanisms triggering the initiation and progression of the disease are, in their complexity, not fully understood and imply the disruption of several tolerance networks. Viral infection is one of the environmental factors triggering diabetes, which is initially based on the observation that the disease’s incidence follows a periodic pattern wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 147 publications
(191 reference statements)
3
34
0
Order By: Relevance
“…TLR3 typically resides in the endosomal compartment and is predominantly restricted to immune cells [ 64 ]. Consistent with this (and noting that the evidence remains equivocal [ 65 ]), we have not been able to detect TLR3 by immunohistochemistry in human beta cells [ 5 ]. By contrast, MDA5 and RIG-I both sense dsRNA species present in the cytoplasm of most cells [ 64 ].…”
Section: Ifns As a Key Link Between Environmental And Genetic Risksupporting
confidence: 81%
“…TLR3 typically resides in the endosomal compartment and is predominantly restricted to immune cells [ 64 ]. Consistent with this (and noting that the evidence remains equivocal [ 65 ]), we have not been able to detect TLR3 by immunohistochemistry in human beta cells [ 5 ]. By contrast, MDA5 and RIG-I both sense dsRNA species present in the cytoplasm of most cells [ 64 ].…”
Section: Ifns As a Key Link Between Environmental And Genetic Risksupporting
confidence: 81%
“…The concept of virus associated diabetes is not new. Already back in 1926, Franklin Adams observed that severe T1D breaks out “immediately after such an infection”, and this has been later confirmed in many large studies ( 16 ). There is a large body of evidence for enteroviral infection initiating the auto-immune response and subsequent β-cell destruction in genetically predisposed individuals, where a viral response is boosted through massive production of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 85%
“…Decorated with a high concentration of pattern recognition receptors, i.e., TLR3/4, RIG-I, MDA-5, and with IL-1R1, and especially vulnerable to inflammatory destruction, the β-cell undergoes apoptosis in response to inflammation, metabolic control derails and diabetes develops. In parallel, the virus initiated interferon response accelerates hyperexpression of surface HLA-I molecules and thus activation of auto-reactive T-cells and auto-immunity against β-cells ( 16 ). Also, β-cell failure in T2D has been associated with chronic subclinical inflammation and elevated cytokines and chemokines, especially IL-1β, IL-6, and CXCL10 levels in proximity to the islet are initiator for β-destruction, dysfunction, and metabolic deterioration ( Figure 1B ) ( 16 , 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The finish DIPP cohort revealed the appearance of islet autoantibodies in a seasonal pattern, with IA following the seasonality of viral infection [45]. A combination of factors in addition to viral infection, including higher inflammation, altered diet, reduced exercise and reduced vitamin D levels have been suggested to influence seasonality of T1D and other autoimmune diseases [120,121].…”
Section: Historical Association Between Ev and T1dmentioning
confidence: 99%